Serological investigation of maedi-visna virus infection in sheep in konya region - Sibel Yavru; Atilla Şimşek; Oya Bulut; Mehmet Kale (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was purposed detecting of presence and seroprevalence of Maedi Visna Virus (MVV) infection of sheep in private flocks in Konya. Materials and Methods: Blood serum samples taken from sheep (different race, age and sex) in Konya and the surrounding in the private sheep farms were used. Samples obtained from flocks analyzed by agar gel immunodiffusion test (AGID) for determine the presence of antibodies against MVV. Results: Thirty nine (2.90%) of 1343 sheep blood serum were found to be positive for the presence of MVV antibodies. Seropositivity rates of flocks were determinated between 0.85-13.33%. When the results were analyzed by race: Seropositivities for Akkaraman and Morkaraman as follows: 36 (2.68%) and 3 (0.22%), respectively. Seropositivity rates by gender were evaluated to be 33 females (2.45%) and 6 males (0.44%). Thirty of 33 seropositive females were Akkaraman and 3 were Morkaraman. Six seropositive males were determined as Akkaraman. Ranges of ages of 39 seropositive sheep were about between 1-2.5 years old. Conclusion: The seroprevalence detected in this study was lower than that in other countries.